Contributions of peak sediment events to annual loads and the effects of best management practices on peak loads in the sub-humid Ethiopian highlands: the Debre Mawi watershed [Abstract only] - Dagnew, D.C.; Guzmán, Christian D.; Tebebu, Tigist Y.; Zegeye, Assefa D.; Akal, Adugnaw T.; Mekuria, Wolde; Ayana, Essayas K.; Tilahun, Seifu A.; Steenhuis, Tammo S. (2015)
Intense rainfall/runoff events produce large proportion of suspended sediment concentrations and sediment load responses. With an aim to mitigate land degradation problems in Ethiopia, soil and water conservation projects are being massively implemented. The effect of these conservation measures in reducing sediment in streams have never been quantified due to unavailability of sediment data. In a quantitative evaluation to quantify the contribution of intense event/daily sediment loads to annual sediment loads and effect of conservation measures in reducing erosion, we monitored three nested experimental sub-watersheds and a 95 ha main watershed in the sub-humid Ethiopian highlands, Debre Mawi watershed for four consecutive years. The contribution of the largest 10–minute events and peak daily sediment loads to annual sediment loads and the effect of Best Management Practices (BMPs) on peak sediment transport processes were evaluated. The contribution of the largest event loads reached up to 22% of the total annual sediment loads. The peak event sediment loads reached up to 11 t ha-1. The contribution of the largest daily sediment load events to annual loads is up to 86%. For the two largest daily sediment load events, the contribution reached up to 95%. The total sediment loads of the two largest daily sediment load events ranged from 40-68 t ha-1day-1 indicating that most of the annual sediment loads are transported with in one or two intense daily sediment load events in the (sub) humid Ethiopian highlands. Comparison of peak sediment loads before and after the implementation of BMPs indicates that conservation practices such as soil bunds, stone faced soil bunds and stone bunds substantially reduced the contribution and magnitude of peak sediment loads. The sediment trap efficiency of the BMPs can be further improved by making ditches deeper than existing practice of 50 cm depth in the Ethiopian highlands.